The psychological well being of breast cancer patients receiving chemotherapytreatmentatthe oncology clinic of Hospital Universiti Sains Malaysia (HUSM) - Ernest, Mangantig (Universiti Sains Malaysia, 2009)
Psychological status is one of the components of the patient's quality of life (QOL), therefore, it is important to determine the patient's psychological well being status since it is one of the indicators for the patient's QOL. Poor psychological well being could influence disease process and response to treatment. Therefore, it is important to supplement information regarding the psychological well being among breast cancer patients receiving chemotherapy treatment as chemotherapy itself would yield many distressing side effects. The objectives of this study are to determine the psychological well being status of breast cancer patients receiving chemotherapy treatment, to determine the association between the psychological well being status and the socio-demographic variables among breast cancer patients and to identifY the relationship between the psychological well being status and the common side effects of chemotherapy treatment. This study is a quantitative and cross-sectional study. Sixty breast cancer patients that were receiving chemotherapy participated in this study. The instrument used is Psychological General Well Being Index with reliability alpha 0.959. Results from this study revealed that 56.7% of the subjects had poor psychological well being status and 43.3% had good psychological well being status. The fmdings showed a significant association between psychological well being status and the socio-demographic variables of age (0.00), marital status (0.04) and number of chemotherapy cycle (0.03). The fmdings also showed a significant relationship between the psychological well being status and the common side effects of chemotherapy treatment (fatigue, alopecia and appetite alteration). As a conclusion, health care providers need to recognize certain socio-demographic factors such as age, marital status and number of chemotherapy cycle that affects the patient's psychological well being status and treatment that is most effective to prevent or treat the side effects of chemotherapy need to be determine to improve the patient's psychological well being status during chemotherapy treatment.